Treatment of chronic periodontitis using a preparation based on plant components in an experiment - G. A. Valeeva; R. R. Haibullina; K. V. Danilko; O. R. Shangina; L. P. Gerasimova; M. R. Shamsiev; M. I. Astakhova; I. A. Galiahmetova (LLC "Endo Press", 2022)
Aim. Development of the chronic periodontitis treatment method using the medicamentation based on herbal components in the experiment.Materials and methods. An experimental model of chronic periodontitis was created. Mesenchymal stem cells (MSC) from the extracted retained human tooth were obtained multipotent. The obtained MSCs were injected into the periodontalpockets together with the osteogenesis stimulator drug. Then a medicamentation based on plant components was applied.Results. Periodontal pocket depth decreased to 1.5 ± 0.01 mm (P < 0.001). There was no tooth mobility. Three months after the therapeutic procedures radiographs of the rats showed signs of bone neoplasia. By 6 months these signs became more pronounced: the foci of stained osteoporosis disappeared and began to acquire a finely petrified structure, the contours of the interalveolar septa became clear and smooth with a simultaneous increase in the height of resorbed ridges of the interalveolar septa.Conclusions. Experimental studies have shown pronounced therapeutic efficacy of the method for the treatment of destructive changes of the alveolar bone in periodontitis.